2019
DOI: 10.1016/j.jdermsci.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miRNA derived from keratinocytes regulates pigmentation in melanocytes

Abstract: Background: Pigmentation is controlled by complex mechanisms. Evidence suggests that miRNAs can regulate pigmentation. However, the mechanism has not been fully elucidated. Objective In this study, we revealed a novel mechanism that regulates pigmentation involving exosomes, miRNAs and the crosstalk between keratinocytes and melanocytes. Methods: The expression and localization of exosome specific marker TSG101 in keratinocytes and melanocytes; Changes of melanin content in melanocytes after co-culture of exos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 41 publications
(46 reference statements)
3
63
0
Order By: Relevance
“…The pathway by which vesicles (exosomes) secreted into the extracellular space function as a means of intercellular communication has been attracting attention in recent years . This scientific concept has facilitated investigations of the transmission of information between keratinocytes and melanocytes and it was reported several years ago that normal human keratinocytes release exosomes that play a role in regulating pigmentation . That study reported that miRNA secreted within exosomes can target melanocytes, resulting in the modulation of their pigmented status by altering levels of gene expression and enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathway by which vesicles (exosomes) secreted into the extracellular space function as a means of intercellular communication has been attracting attention in recent years . This scientific concept has facilitated investigations of the transmission of information between keratinocytes and melanocytes and it was reported several years ago that normal human keratinocytes release exosomes that play a role in regulating pigmentation . That study reported that miRNA secreted within exosomes can target melanocytes, resulting in the modulation of their pigmented status by altering levels of gene expression and enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miR‐675 was detected in the media from keratinocyte cultures and was suggested to be possibly released from keratinocytes as one type of inclusion in exosomes, and to be involved in regulating melanogenesis by melanocytes through effects on microphthalmia‐associated transcription factor (MITF) as a target . In addition to miR‐675, the effect of miR‐330‐5p derived from the keratinocytes' exosome on melanocyte pigmentation was also verified recently . Furthermore, another study suggested that keratinocytes regulate melanocyte pigmentation by modulating their miRNA content in exosomes …”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Exosomes are common EVs originated form endosomes with a diameter of 30-150 nm [6,7], and they carry numerous biological substances, such as proteins, mRNAs, microRNAs (miRNAs), cytokines, and transcription factors [8]. Studies have shown that melanocytes are the target of exosomes secreted by other cells, such as keratinocytes [9][10][11]; as for exosomes derived from melanocytes, their role in other cells is rarely investigated. Solar radiation stimulates the synthesis of melanin in melanocytes and the transport of melanin-containing melanosomes to neighboring epidermal cells, resulting in skin pigmentation.…”
Section: Introductionmentioning
confidence: 99%
“…17 However, some miRNAs from keratinocyte exosomes negatively regulate melanogenesis in melanocytes, such as miR-330-5p and miR-675. 20,21 In vitiligo, we investigated whether exosomes derived from keratinocytes still have the ability to modulate melanogenesis in melanocytes. Our study revealed that exosomes secreted by VLK have a weaker capacity for promoting melanogenesis of melanocytes.…”
mentioning
confidence: 99%